DAMPAK KEBIJAKAN PEMERINTAH TERHADAP PEMBERDAYAAN DAN PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN PURWAKARTA - Mubarok, Imam; Pujiati, Amin; Maya Nihayah, Dyah (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2024)
This study uses secondary data and qualitative descriptive methodologies to investigate how government policies affect the growth and empowerment of MSMEs in Purwakarta Regency. The study's findings demonstrate that although the government has aided the MSME sector, obstacles such low productivity, lack of product certification, administrative restrictions, and access to technology and skills continue to impede the expansion of MSMEs in Purwakarta Regency. This suggests that more efficient policies are required to boost MSMEs' share of the regional and national GDP.